Subarachnoid hemorrhage triggered by spinal cord vascular malformation in a pediatric patient: case report and review of literature - Ye Zhang; Liaoyuan Zheng; Yongwei Huang; Zongping Li; Jing Feng (Frontiers in Surgery)
BackgroundSpinal cord vascular malformations (SCVMs) in children are relatively rare and present unique challenges due to their distinct physiological characteristics. These malformations often manifest with nonspecific clinical symptoms, increasing the likelihood of misdiagnosis. The treatment of pediatric SCVMs requires a tailored approach, with the choice between microsurgical intervention and endovascular embolization depending on the specific type of malformation and individual patient factors.Case reportWe report a case of a 6-year-old male who presented with a sudden onset of headache. Initial cranial imaging did not reveal any significant intracranial vascular malformations. However, thoracic spine magnetic resonance imaging (MRI) identified an abnormal signal, and digital subtraction angiography (DSA) confirmed the diagnosis of SCVMs. The patient underwent microsurgical treatment and was discharged in good health. Follow-up DSA confirmed the complete resolution of the vascular malformations.ConclusionThis case, along with a review of the literature, underscores the importance of thorough spinal evaluations in pediatric patients with spontaneous intracranial hemorrhage, especially when intracranial vascular malformations are not identified. A high index of suspicion for SCVMs is crucial. Early and accurate diagnosis, followed by appropriate treatment through microsurgical resection or endovascular embolization, can significantly improve therapeutic outcomes in children with SCVMs.